The Effect of Scrapbook Media on Students' Writing Recount Text Ability at the Eleventh Grade of SMA Negeri 1 Tukka in 2021/2022 Academic Year - Ria Anzelina Simanjuntak (JURNAL LINER (Language Intelligence and Educational Research), 2022)
ABSTRACT: The purposes of this research are to find out: 1) the extent of using scrapbook media in teaching writing recount text at the eleventh grade students of SMA Negeri 1 Tukka in 2021/2022 academic year. 2) the extent of the students’ writing recount text before and after using scrapbook media on students’ writing recount text ability at the eleventh grade students of SMA Negeri 1 Tukka in 2021/2022 Academic Year. 3) whether there is a significant effect of using scrapbook media on students’ writing recount text ability at the eleventh grade students of SMA Negeri 1 Tukka in 2021/2022 Academic Year. The population of this research were all the eleventh grade students of SMA Negeri 1 Tukka is 203 students. The research sample was the eleventh MIA 2 students, which consist of 36 students who were taken by purposive sampling. The data collection technique used the observation sheet and test. The results of this research: 1) The use of scrapbook media is 3.7, it is categorized “very good” criterion. 2) The mean score of the students’ writing recount texy ability before using scrapbook media is 61.33, it is categorized “enough”. Meanwhile, after using scrapbook media was 81.3 it was categorized “very good”. 3) the results of data analysis showed that the ttest is higher than ttable (ttest 17.75 > ttable 2.03). So, the hypothesis was accepted. It means that there is a significant effect of scrapbook media on students’ writing recount text ability at the eleventh grade of SMA Negeri 1 Tukka in 2021/2022 academic year. Keywords: Scrapbook Media, Writing Recount Text ABSTRAK: Tujuan penelitian ini adalah untuk mengetahui: 1). Sejauh mana penggunaan media scrapbook dalam pengajaran menulis teks rekon pada siswa kelas sebelas SMA Negeri 1 Tukka Tahun Pelajaran 2021/2022. 2). Sejauh mana kemampuan menulis teks rekon siswa sebelum dan sesudah menggunakan media scrapbook terhadap kemampuan menulis teks rekon siswa pada kelas sebelas SMA Negeri 1 Tukka Tahun Pelajaran 2021/2022. 3). Apakah ada pengaruh yang signifikan penggunaan media scrapbook terhadap kemampuan menulis rekon teks siswa pada siswa kelas sebelas SMA Negeri 1 Tukka Tahun Pelajaran 2021/2022. Populasi dalam penelitian ini adalah seluruh kelas sebelas SMA Negeri 1 Tukka yaitu 203 siswa. Sampel penelitian ini adalah siswa kelas sebelas MIA 2 yang berjumlah 36 siswa yang diambil secara purposif. Teknik pengumpulan data menggunakan lembar observasi dan tes. Hasil penelitian ini: 1) Penerapan media scrapbook adalah 3.7, termasuk kriteria “sangat baik”. 2) Rata rata skor kemampuan teks rekon menulis siswa sebelum menggunakan media scrapbook adalah 61.33 dikategorikan “cukup”. Sedangkan setelah menggunakan media scrapbook adalah 81.33 dikategorikan “sangat baik”. 3) hasil analisis data menunjukkan bahwa thitung lebih besar dari ttabel (thitung 17.75 > ttabel 2.03). Jadi, hipotesis diterima. Artinya ada pengaruh yang signifikan media scrapbook terhadap kemampuan menulis teks rekon siswa pada siswa kelas sebelas SMA Negeri 1 Tukka tahun ajaran 2021/2022.Kata Kunci:Scrapbook Media, Writing Recount Text